Dilute concentrations of maritime fuel can modify sediment reworking activity of high‐latitude marine invertebrates - Thomas J. Williams; David Blockley; Andrew B. Cundy; Jasmin A. Godbold; Rebecca M. Howman; Martin Solan (Ecology and Evolution)
Abstract Multiple expressions of climate change, in particular warming‐induced reductions in the type, extent and thickness of sea ice, are opening access and providing new viable development opportunities in high‐latitude regions. Coastal margins are facing these challenges, but the vulnerability of species and ecosystems to the effects of fuel contamination associated with increased maritime traffic is largely unknown. Here, we show that low concentrations of the water‐accommodated fraction of marine fuel oil, representative of a dilute fuel oil spill, can alter functionally important aspects of the behaviour of sediment‐dwelling invertebrates. We find that the response to contamination is species specific, but that the range in response among individuals is modified by increasing fuel concentrations. Our study provides evidence that species responses to novel and/or unprecedented levels of anthropogenic activity associated with the opening up of high‐latitude regions can have substantive ecological effects, even when human impacts are at, or below, commonly accepted safe thresholds. These secondary responses are often overlooked in broad‐scale environmental assessments and marine planning yet, critically, they may act as an early warning signal for impending and more pronounced ecological transitions.